Follicular lymphoma international prognostic index 2: a new prognostic index for follicular lymphoma developed by the international follicular lymphoma prognostic factor project - Federico, Massimo; Bellei, Monica; Marcheselli, Luigi; Luminari, Stefano; Lopez-Guillermo, Armando; Vitolo, Umberto; Pro, Barbara; Pileri, Stefano; Pulsoni, Alessandro; Soubeyran, Pierre; Cortelazzo, Sergio; Martinelli, Giovanni; et al. (Journal of clinical oncology, 2009)
The aim of the F2 study was to verify whether a prospective collection of data would enable the development of a more accurate prognostic index for follicular lymphoma (FL) by using parameters which could not be retrospectively studied before, and by choosing progression-free survival (PFS) as principal end point. Between January 2003 and May 2005, 1,093 patients with a newly diagnosed FL were registered and 942 individuals receiving antilymphoma therapy were selected as the study population. The variables we used for score definition were selected by means of bootstrap resampling procedures on 832 patients with complete data. Procedures to select the model that would minimize errors were also performed. After a median follow-up of 38 months, 261 events for PFS evaluation were recorded. beta2-microglobulin higher than the upper limit of normal, longest diameter of the largest involved node longer than 6 cm, bone marrow involvement, hemoglobin level lower than 12 g/dL, and age older than 60 years were factors independently predictive for PFS. Using these variables, a prognostic model was devised to identify three groups at different levels of risk. The 3-year PFS rate was 91%, 69%, and 51% for patients at low, intermediate, and high risk, respectively (log-rank = 64.6; P < .00001). The 3-year survival rate was 99%, 96%, and 84% for patients at low, intermediate, and high risk, respectively (P < .0001). Follicular Lymphoma International Prognostic Index 2 is a simple prognostic index based on easily available clinical data and may represent a promising new tool for the identification of patients with FL at different risk in the era of immunochemotherapy.